Observation of high‐frequency electrostatic waves in the vicinity of the reconnection ion diffusion region by the spacecraft of the Magnetospheric Multiscale (MMS) mission. Issue 10 (27th May 2016) - Zhou, M.; Ashour‐Abdalla, M.; Berchem, J.; Walker, R. J.; Liang, H.; El‐Alaoui, M.; Goldstein, M. L.; Lindqvist, P.‐A.; Marklund, G.; Khotyaintsev, Y. V.; Ergun, R. E.; Wilder, F. D.; et al.
Abstract: We report Magnetospheric Multiscale observations of high‐frequency electrostatic waves in the vicinity of the reconnection ion diffusion region on the dayside magnetopause. The ion diffusion region is identified during two magnetopause crossings by the Hall electromagnetic fields, the slippage of ions with respect to the magnetic field, and magnetic energy dissipation. In addition to electron beam modes that have been previously detected at the separatrix on the magnetospheric side of the magnetopause, we report, for the first time, the existence of electron cyclotron harmonic waves at the magnetosheath separatrix. Broadband waves between the electron cyclotron and electron plasma frequencies, which were probably generated by electron beams, were found within the magnetopause current sheet. Contributions by these high‐frequency waves to the magnetic energy dissipation were negligible in the diffusion regions as compared to those of lower‐frequency waves. Key Points: Ion diffusion region was identified by MMS spacecraft in the Earth's dayside magnetopause High‐frequency electrostatic waves were observed in the vicinity of the ion diffusion region Energy dissipated by these high‐frequency waves is negligible compared to that by the lower‐frequency process